Analysis of the Use of ICT in the Classroom: Comparative Study Colombia, Peru, Mexico and Spain - Cipagauta Moyano, Marisol Esperanza; Flórez Orozco, Dallanis Fernanda; Medina Agudelo, Leydi Stefania (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This research article addresses the use of ICT in the classroom: a comparative study between Colombia, Peru, Mexico and Spain, developed under a mixed approach. It should be noted that ICTs are currently immersed in all areas of life. In this way, a comparative analysis is made of the four countries where the perception survey was applied with the intention of identifying in each one, the use that is given to ICT and the way in which teachers use them in their classrooms. basic, secondary and higher education.